Introduction to the Cereals & Europe Focus Issue. Issue 4 (23rd July 2014) - Brijs, Kristof; Pareyt, Bram
ABSTRACT: In May 2013, the Laboratory of Food Chemistry and Biochemistry, KU Leuven, organized the 4th Cereals & Europe Spring Meeting in the university's hometown Leuven, Belgium. The C&E Spring Meeting was endorsed by AACC International and its European Section, Cereals & Europe, and partially sponsored by key companies such as platinum‐level sponsor Puratos, gold‐level sponsors Chopin Technologies, CSM, DSM, DuPont, Kellogg, and Perten Instruments, and silver‐level sponsors Bühler, Cargill, Megazyme, Nestlé, and Novozymes. It was attended by more than 200 cereal scientists and technologists from 24 countries representing both academia and industry. The C&E Spring Meeting's theme was "Unlocking the Full Potential of Cereals: Challenges for Science Based Innovation." The program, hence, focused on different aspects of cereals related to corporate challenges and new technologies, which were explored during 55 oral presentations and 56 poster presentations and reflected in six major session topics: cereal biotechnology; cereal constituents and ingredients; cereal‐based food production and processing; structure–function relationships; analytical aspects; and nutritional aspects of cereal‐based foods, food processing, and ingredients. There is obviously great potential in exploiting cereals as a tool to address the challenges of science‐based innovation. One of these challenges is reflected in the interest of today's consumers in the relationship between food and health. Here, genetic and molecular approaches can be used to improve both the content and composition of health‐promoting constituents in cereals. Other challenges the industry faces include increased incidence and/or diagnosis of celiac disease, wheat allergies, and gluten sensitivity. Not surprisingly, the quest for alternative cereals, ingredients, and products that meet the needs of consumers facing these intolerances, allergies, or sensitivities is ongoing and becomes more and more important. Alternatively, thoroughly understanding the changes in cereal constituents and ingredients during food production and processing as well as their structure–function relationships will allow cereal scientists to alter their properties. This, in turn, will provide a means of meeting new nutritional, structural, and textural criteria. Examples include the challenges associated with increasing the amount of dietary fiber in a formulation, replacing gluten with other proteins, and improving the eating characteristics of both fresh and stored (as a result of improved shelf life) products. Understanding the structural and textural properties and relating them to (often biopolymer) constituent and ingredient properties present some interesting challenges. However, there is more to the story than this. Modern cereal research ends neither at the moment at which food products are produced nor at the moment at which their properties have been analyzed. It also digs further into and focuses increasingly on what happens to foods and their constituents within the gastrointestinal tract. By doing so, cereal research increasingly aims at catching sight of the direct relationship between food, food digestion, and human health. Despite advances in each of the aforementioned topics, significant challenges in cereal research still need to be addressed. In doing so, cereal researchers in both academia and industry should keep in mind that consumer demands are constantly changing. We here have selected six peer‐reviewed papers from the 2013 C&E Spring Meeting: Effects of Genotype and Environment on Phenolic Acids Content and Total Antioxidant Capacity in Durum Wheat. D. Martini, F. Taddei, I. Nicoletti, R. Ciccoritti, D. Corradini, and M. G. D'Egidio Effect of High‐Pressure Processing on the Features of Wheat Milling By‐products. A. Marti, A. Barbiroli, F. Bonomi, A. Brutti, S. Iametti, M. Marengo, M. Miriani, and M. A. Pagani Effect of Wheat Grain Steaming and Washing on Lipase Activity in Whole Grain Flour. J. L. De Almeida, B. Pareyt, L. R. Gerits, and J. A. Delcour Ultrasonic Characterization of Unyeasted Bread Dough of Different Sodium Chloride Concentrations. F. Koksel, A. Strybulevych, J. H. Page, and M. G. Scanlon Correlation of Quality Parameters with the Baking Performance of Wheat Flours. S. M. Thanhaeuser, H. Wieser, and P. Koehler Study of the Chemical Changes and Evolution of Microbiota During Sourdoughlike Fermentation of Wheat Bran. F. Manini, M. Brasca, C. Plumed‐Ferrer, S. Morandi, D. Erba, and M. C. Casiraghi The papers included in this focus issue demonstrate that the 2013 C&E Spring Meeting brought together multidisciplinary perspectives. We hope that they can serve as a basis for further discussions between cereal researchers from both academia and industry and help them to fully unlock the potential of cereals to address the present corporate challenges to science‐based innovation. We thank all of the speakers, attendees, session chairs, sponsors, participants, and team members of the Laboratory of Food Chemistry and Biochemistry. Click onCurrent Issues on left and thenJuly/August 2014 to view the six articles noted above. (From the Mobile site, go to the July/August 2014 issue.)